Pengaruh Strategi Peningkatan Pengawasan Lingkungan Taman Kanak-Kanak (TK) terhadap Perkembangan Anak di PAUD Kusuma - Andriani Andriani; Chientya Annisa Rahman Putrie (Neolectura, 2021)
Education is one way to develop children's skills and abilities. Child development is the center of attention of parents and teachers. How not? The development of children sooner or later will affect the child in particular and parents in general. No child grows up by itself. Therefore, this study aims to determine the effect of the strategy to increase the supervision of the kindergarten environment on the development of children in PAUD Kusuma. This research is a descriptive and associative research with a quantitative approach. The population and sample in this study were teachers and children of class A PAUD Kusuma as many as 82 people. The sampling technique used is simple random sampling. Data collection techniques used are observation, questionnaires, and documentation. The data analysis technique used is descriptive statistics and inferential statistics. This data analysis technique consists of instrument testing (validity test and reliability test), classical assumption test (data normality test, heteroscedasticity test, autocorrelation, multicollinearity), regression analysis, coefficient of determination analysis, and hypothesis testing. Descriptive statistical analysis and inferential statistics were processed using the Statistical Product for Service Solution (SPSS) 16.0 for windows program. The results of the study indicate that there is an effect of the strategy of increasing the environmental supervision of kindergarten on the development of children in PAUD Kusuma.